Assessment of the likelihood of exceeding the flare capacity of multiple LNG processing trains. Issue 3 (29th October 2014) - Lopez, Ricardo A.; Saud, Yaneira; Vaez, Najmeh
<x xml:space="preserve">Abstract</x> Flare systems are typically designed to meet recognized and generally accepted good engineering practice for foreseeable vent and relief scenarios. API 521 [American Petroleum Institute, ANSI/API Standard 521 Guide for Pressure‐Relieving and Depressuring Systems: Petroleum Petrochemical and Natural Gas Industries, Fifth Edition, American Petroleum Institute, 2007] allows for multitrain units to be protected by the same flare system. Therefore, these systems must be reliable, available, auditable, and maintainable. However, any designer's concern should be the possibility of a common‐cause failure (CCF) that impairs several safeguards or causes a plant‐wide failure. A shutdown incident can result in flare relief demands that are higher than the designed capacity. CCF is defined as a failure of more than one device, function, or system due to the same cause. Examples of common causes are errors in design, installation, maintenance, or operation of redundant components. To ensure that the designed flare capacity for a Liquefied Natural Gas (LNG) facility is appropriate, it is necessary to assess the frequency of relieving combinations that have the potential of exceeding flare capacity during a shutdown which is the result from a CCF. A common practice for this purpose is to perform probabilistic risk assessment using fault tree analysis (FTA) techniques during the front‐end engineering design stage. However, CCFs are rarely or not commonly considered in the analysis. CCFs might have a significant impact on the final calculations, resulting in probabilities of overloading the flare system by one or more orders of magnitude greater, with the potential of not meeting the project's tolerability threshold. The analysis starts with the identification of CCF scenarios resulting in relief loads from one and multiple trains. Following the identification of these scenarios, the frequency of such events is quantified and compared with each facility's tolerability threshold. Historical data from published sources were used to calculate the likelihood for both CCFs and their impacts. A FTA was used to illustrate the various outcomes that may arise from a CCF producing simultaneous reliefs. The scope of each analysis included a facility in multitrain operation with common infrastructure and supporting utility systems. A one train (initial startup case) analysis was done for a baseline comparison, and different scenarios were then analyzed for potential flare overload (e.g., gas compressors from two or more trains failing to stop on demand once blowdown has started, coupled with feed gas valves failing to close). Finally, the probability of exceeding the flare capacity and the associated consequences were compared against the project's qualitative risk assessment matrix to determine if the probability of flare exceedance was tolerable. © 2014 American Institute of Chemical Engineers Process Saf Prog 34: 250–258, 2015